2021
DOI: 10.1177/10887679211046866
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Histories of Intimate Partner Homicide Offenders

Abstract: This exploratory study investigates intimate partner homicide (IPH) offenders’ criminal histories to examine opportunities for criminal justice system intervention. Data were collected from the Michigan Violent Death Reporting System and Michigan State Police for the 117 IPHs committed in 2014 and 2015 in Michigan. Descriptive statistics on types of criminal charges and convictions for the 103 IPHs committed by aggressors (e.g., not in self-defense) are presented, with relatively few domestic violence charges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…That being said, males are the primary perpetrators of both intimate partner homicide and homicide-suicide (Zeppegno et al, 2019). Relatedly, male perpetrators of intimate partner homicide and homicide-suicide more often than not have a history of (non-lethal) domestic violence; and males more readily use firearms than females, particularly in disadvantaged areas with pervasive violence (Zeoli et al, 2021). Given this confluence of gender dynamics, firearms, and social context, it is important to continue to use federal and local gun control measures to restrict access to firearms by male domestic violence offenders (Raissian, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That being said, males are the primary perpetrators of both intimate partner homicide and homicide-suicide (Zeppegno et al, 2019). Relatedly, male perpetrators of intimate partner homicide and homicide-suicide more often than not have a history of (non-lethal) domestic violence; and males more readily use firearms than females, particularly in disadvantaged areas with pervasive violence (Zeoli et al, 2021). Given this confluence of gender dynamics, firearms, and social context, it is important to continue to use federal and local gun control measures to restrict access to firearms by male domestic violence offenders (Raissian, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Perpetrators of intimate partner homicide disproportionately have a history of interpersonal violence and are known to the criminal justice system (Vignola-Lévesque & Léveillée, 2022). Accordingly, previous intimate partner violence is the most documented correlate of intimate partner homicide (Zeoli et al, 2021). When a record of intimate partner violence does not precede intimate partner homicide, it is likely due to a lack of reporting to authorities rather than to its absence (Matias et al, 2021).…”
Section: Intimate Partner Homicide: a Brief Review Of The Existing Li...mentioning
confidence: 99%
“…Criminal history : Criminal history was not included in the study from our initial research [ 26 ], because of the scarce number of cases that allowed us to obtain reliable results. Evidence from several studies found that IPV offenders had high rates of prior criminal history [ 74 , 75 ], particularly in intimate partner homicide (IPH) cases [ 76 ]. The cases for weapon possession by the defendant were analyzed, verifying the inexistence of differences between groups and that it was not a determinant in mandatory SRP.…”
Section: Discussionmentioning
confidence: 99%
“…However, weapon possession, namely firearms, among male partners with a history of IPV is a lethal risk factor for the IPH [ 77 ]. It doubles the risk of an intimate partner´s attempted or consummated murder [ 56 58 , 65 , 76 , 78 ]. Such an outcome may be dependent on the state prosecutor´s assessment of the risk levels in the case and consideration of applying other heavier, and hazard-adjusted legal measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation